PENGARUH TINGKAT PEMBERIAN KOMPOS TERHADAP KEBUTUHAN AIR TANAMAN BEBERAPA JENIS KACANG - Frans Azarya Simanjuntak; I Wayan Tika; Sumiyati Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2013)
The aim of this research is to understand the effect of provision rates of dosage compost in crop water requirements for several types of beans. There are seven levels of soil and compost ratio, there are: soil 100%, 97.5% soil: 2.5% compost, 95% soil: 5% compost; 92.5% soil: 7.5%. compost 90% soil: 10 % compost; 87.5% soil: 12.5% compost and 85% soil: 15% compost. The research was analyzed descriptively. Parameters observed in this research were the field capacity, permanent wilting point, availability of water, crop water requirements. The result of this research indicate that the provision rates of compost in several types of beans affected the water availability. For cowpea ranged from 34,4% - 42,7%, soybeans ranged from 42,3% - 48,6%, green beans ranged from46,7% – 55,7%. Crop water requirements varied depend on the type of the beans. The ratio of soil and compost 85%:15% for cowpea cultivation soybean and green beans is the best in resulting low crop water requirement.